Analisis fungsi dan bentuk kata umpatan dubbing indonesia platform disney hotstar dalam film home alone 1 - Faz, Najma Tsuroyya (Maliki Interdisciplinary Journal, 2026)
Swear words are very familiar in society and have even become a common part of movies. Home Alone 1 is one movie in which the characters use many swear words in their dialogue. The purpose of this study is to identify and provide an understanding of the functions and forms of swear words. The method used is qualitative research by collecting data from the film through the technique of watching and taking notes. The results of the analysis show that there are four functions of swear words: abusive, expletive, auxiliary, and humorous. The forms of swear words are divided into eight types, namely swear words related to animals, swear words related to professions, swear words related to kinship, supernatural beings, objects, activities, swear words related to circumstances or conditions, and swear words related to body parts. This study reveals how swear words are used in contexts appropriate for the target audience, which in this case is children, while maintaining the emotional essence of the original film. Thus, this study provides insight into the use of swear words in dubbing.